The Effect Of Hydrotherapy (Drinking Water) On The Reduction Of Blood Glucose Levels In Type 2 Diabetes Mellitus Patients - Endang Soelistyowati; Mohammad Najib; Nur Hasanah; Dilla Illiyin Saffanatul Hikmih; Mohammed Ismath (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
a chronic metabolic illness marked known as type 2 diabetes mellitus (DM) is characterised by persistent hyperglycemia brought on by either insulin resistance or inadequate insulin production. This study examines the effect of hydrotherapy—specifically the daily consumption of plain water—on blood glucose levels in individuals with DM. Utilizing a one-group pretest-posttest pre-experimental design, 51 randomly selected participants consumed 1.5 liters of plain water each morning for seven consecutive days, no later than 15 minutes before breakfast. The study aims to evaluate water intake as a potential supportive intervention in managing blood glucose. Data examined with the Wilcoxon Signed Rank Test showed a substantial drop in blood glucose levels following the hydrotherapy session (p-value = 0.000 < α = 0.05). The outcomes of this study show that the incorporation of plain water consumption within the framework of hydrotherapy demonstrates a significant potential in minimizing blood glucose levels among individuals diagnosed with type 2 DM. This suggests that hydrotherapy, when complemented by adequate water intake, may serve as an effective, non-pharmacological intervention for managing glycemic control in diabetic patients. As such, it may serve as an independent nursing intervention to help prevent complications associated with the condition.